1991
DOI: 10.1002/prac.19913330204
|View full text |Cite
|
Sign up to set email alerts
|

Zur Reaktion von 2‐Aminothiophen‐3‐carbonitrilen mit Heterocumulenen

Abstract: The Reaction of 2‐Aminothiophene‐3‐carbonitriles with Heterocumulenes. The reaction of 2‐aminothiophene‐3‐carbonitriles (1) with phenyl isothiocyanate does not yield the expected thieno[2,3‐d]pyrimidine derivatives but the substituted dithieno‐[2′,3′:4, 3][2′,3′:8, 9]pyrimido[3, 4‐a]pyrimid‐7‐thiones (4). The compounds 4 also may be synthesized from 1 and thiophosgene. Analogously, from 1 and phenyl isocyanate the substituted dithieno[2′,3′:4, 3][2′,3′:8, 9]pyrimido[3, 4‐a]pyrimid‐7‐ones (9) arise in small yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Treatment of compounds 1a or 2a with carbon disulfide in 10% ethanolic sodium hydroxide solution afforded the thieno [2,3- The structures of compounds 5 and 8 were substantiated from their spectral data and they were rigidly confirmed by mp comparison with that reported [1,3]. However, the structures of compounds 6 and 7 were deduced spectroscopically as well as chemically in the former one.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Treatment of compounds 1a or 2a with carbon disulfide in 10% ethanolic sodium hydroxide solution afforded the thieno [2,3- The structures of compounds 5 and 8 were substantiated from their spectral data and they were rigidly confirmed by mp comparison with that reported [1,3]. However, the structures of compounds 6 and 7 were deduced spectroscopically as well as chemically in the former one.…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported [1] that 2-amino-3-cyano-4,5,6,7-tetrahydrobenzo [b]thiophene 1a reacted with phenylisocyanate in DMF and carbon disulfide in pyridine to give dithienopyrimidopyrimidinone and thienopyrimidinedithione beside dithienopyrimidopyrimidinethione, respectively. However, Sukumaran and Rajasekharass [2] reported the formation of thienothiazine upon treating 1a with carbon disulfide in pyridine.…”
Section: Introductionmentioning
confidence: 99%
“…A literature survey revealed that an analogous compound was produced under similar reaction conditions. 21 A suggested mechanism for the formation of the title compound is shown in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of ethyl 2-amino-5-benzoyl-1H-pyrrole-3-carboxylate (55) and its use for the synthesis of 2-thioxopyrimidine-containing condensed derivatives were described in the work by Danswan et al 38 Thus, it was shown that interaction of compound 55 with ethyl isothiocyanate yielded 6-benzoyl-3-ethyl-2-thioxo-2,3-dihydro-1H-pyrrolo- An interesting transformation was published by Gewald and his colleagues. 40 They explored the reaction of 2-aminothiophene-3-carbonitrile and its substituted derivatives 64 with phenyl isocyanate (Scheme 17). It was established that unlike in some previously described similar cases (cf.…”
Section: [5+1] Heterocyclizationmentioning
confidence: 99%